Design, Development, and Optimization of Novel Proniosomes for Enhanced Transdermal Delivery of Eprosartan Mesylate (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The present novelty in the fabrication work is preparation of proniosomal gel using eprosartan mesylate usingcoacervation phase separation technique. Materials and Methods: In the present work made, the formulations wereprepared using drug along with excipients such as span 60, tween 80, lecithin, cholesterol, carbopol 934, alcohol, andglycerin. A total of six formulations on gels were prepared by coding EF1 to EF6. The drug and polymer interactionstudies by Fourier transform infrared (FTIR) were carried before formulating the preparation composition. Thegel formulations were evaluated for physicochemical evaluation such as scanning electron microscopy, percentageentrapment efficiency (EE), pH, rheological measurements, homogeneity, extrudability, spreadability, and in vitrodrug release study. Results and Discussion: The formulation EF3 which was composed with drug, eprosartanmesylate 60 mg, lecithin 450 mg, cholesterol 100 mg, alcohol 0.5 mg, and carbopol 934 - 2% has shown optimumrelease in concentration independent manner. The in vitro drug release profile for formulation EF3 at 24 h was98.43% and shown maximum drug release from the gel. The % EE was 89.43 ± 1.57, pH 7.04 ± 0.15, viscosity35.46 (Pa S), and the shape, surface, and size characteristics of the optimized formulation EF3 were observed undera scanning electron microscope. The structure of the formed vesicle was studied by spreading as a thin layer on aglass slide. The images were taken using a Fujifilm Finepix F 40 fd 8.3 MP computer camera with a 3-inch opticalzoom. Conclusion: Hence, prepared proniosomal gel of eprosartan mesylate could be promising drug delivery asthey minimize the dose, overcome the side effects, simplify treatment regimen, and improve patient compliance